A strip cut in a composite elastic wedge. Issue 4 (2016) - Pozharskii, D.A.
Abstract: Integral equations of new three-dimensional problems concerning a cut in the plane of symmetry of a composite elastic wedge are obtained. The wedge consists of three wedge-shaped layers with a common apex, connected by a sliding clamp: in the middle there is a compressible layer with a cut, to the sides of which two identical incompressible layers are pressed. For the case of a strip cut emerging on the edge of the composite wedge, using the method of paired integral equations, the problem is reduced to Fredholm integral equations of the second kind. An expression is obtained for the stress intensity factor.